Memorandum on maternal mortality - Labour Party (Great Britain). Advisory Committee on Public Health
1928-07 1928 1920s 10 pages Private and Confidential July, 1928. No. 161/a. LABOUR PARTY RESEARCH AND INFORMATION DEPARTMENT PUBLIC HEALTH ADVISORY COMMITTEE Memorandum on MATERNAL MORTALITY I. LEGAL POWERS The Laws and Regulations providing for the care of mothers are as follows:- Local authorities (1) The Public Health Act (1875) - gave Local Authorities powers to build maternity hospitals, among other hospitals. Also Section 131 empowered a Local Authority to arrange for the reception in a hospital of sick inhabitants of their district, on payment of an agreed sum. Difficulty arose over the finance of such schemes, and there was question about the provision of special accommodation at voluntary hospitals to whose funds a Local Authority had paid subscriptions in response to a general appeal. (2) The Public Health Act (1925) - Section 64 authorised reasonable subscriptions by the Local Authority if it was satisfied of the adequacy of accommodation provided for sick inhabitants of its district. Expenditure under this section is limited. (3) The Midwives Act (1902) - made County Councils the local supervising authorities for midwives, and gave them powers of delegation. The Local Sanitary Authority must investigate charges of malpractice, negligence or misconduct, suspend from practice, if necessary, and report to the Central Midwives Board addresses of midwives practising in its area, and of any suspended from practice. (4) The Midwives Act (1918). Enables The Local Sanitary Authority [may] to aid the training of midwives and make grants for this purpose. It may also recover fees from the patient when a doctor has been called in by the midwife. (5) The Midwives and Maternity Homes Act (1926) - gives additional 292/824/1/121